Quality of the femoral cement mantle in total hip arthroplasty using the direct anterior hip approach - Eustathios Kenanidis, MD, MSc, PhD (Arthroplasty Today, 2020)
Background: Limited literature exists concerning the femoral cement mantle quality that can be achieved through an anterior approach in total hip arthroplasty (THA). We radiologically evaluated the quality and thickness of the femoral cement mantle in patients undergoing THA utilizing the direct anterior approach (DAA). Methods: Immediate postoperative anteroposterior and lateral radiographs of 116 consecutive patients who underwent hybrid or fully cemented THA using the DAA and cemented Quadra-C stem (Medacta, International, SA, Switzerland) were assessed by 2 arthroplasty surgeons blinded to the study. Surgical indications were hip osteoarthritis or subcapital hip fracture. The cement mantle and stem alignment were evaluated using the Barrack classification and Khalily methods, respectively. After calibration of radiographs, the thinnest part of the cement mantle per Gruen zone was recorded. Parameters were compared between obese and nonobese patients. Results: Agreement between raters was substantial for the cement quality in anteroposterior (k = 0.707, P ≤ .001) and moderate for lateral radiographs (k = 0.574, P ≤ 001). The cement mantle was graded A in 39.25%, B in 53.0%, and C in 7.75% of anteroposterior radiographs and similarly for lateral radiographs (40.1% A, 51.75% B, 9.5% C). 93% of stems had neutral alignment. The mean thinnest cement mantle (P = .237) and incidence of inadequate cement mantle (<2 mm) per zone (P = .431) were comparable between Gruen zones. The cement mantle quality (P = .174) and inadequacy (P > .05) and stem alignment (P = .652) were comparable between obese and nonobese patients. Conclusions: DAA enables correct implantation and effective cementation of straight femoral stems. A high-quality cement mantle can be achieved using DAA even in obese patients.